2001
DOI: 10.1046/j.1365-2826.2001.00726.x
|View full text |Cite
|
Sign up to set email alerts
|

Oestradiol Microimplants in the Ventromedial Preoptic Area Inhibit Secretion of Luteinizing Hormone via Dopamine Neurones in Anoestrous Ewes

Abstract: Oestradiol exerts a season-specific negative feedback effect on the GnRH/LH neurosecretory system of the Suffolk ewe. This neuroendocrine suppression is mediated in part by dopamine A15 neurones, but these neurones do not possess the oestrogen receptor. Based on indirect evidence, we hypothesized that oestrogen receptor-containing neurones in the ventromedial preoptic area (vmPOA) may be the initial step in a neuronal system whereby oestradiol suppresses GnRH secretion during the non-breeding season. To test t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 56 publications
1
46
0
Order By: Relevance
“…E 2 -containing microimplants placed in the MPOA also suppressed pulsatile GnRH/LH secretion during anestrus, and sulpiride (a dopamine antagonist) disrupted this suppression [22]. It was reported that the ERα-expressing neurons predominate in this region [37, 40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…E 2 -containing microimplants placed in the MPOA also suppressed pulsatile GnRH/LH secretion during anestrus, and sulpiride (a dopamine antagonist) disrupted this suppression [22]. It was reported that the ERα-expressing neurons predominate in this region [37, 40].…”
Section: Discussionmentioning
confidence: 99%
“…Expression of ERβ has been found in GnRH neurons, however, until now, only in rodents [16, 17]. Considerable evidence indicates that the positive or negative effects of E 2 on the GnRH neuronal system in sheep are mediated by interneurons and/or the glial matrix [18, 19, 20, 21, 22]. E 2 has also been shown to be a most potent drug stimulating prolactin (PRL) release.…”
Section: Introductionmentioning
confidence: 99%
“…We stereotaxically implanted an 18-gauge stainless steel guide tube (n ϭ 10, experiment 2) into the third ventricle using sterile techniques and gas anesthesia (4 parts oxygen: 1 part nitrous oxide, supplemented with halothane at 1-4%) as previously described (27). Briefly, a 2-cm diameter hole was drilled in the skull, the sagittal sinus ligated, and radioopaque dye injected into one lateral ventricle.…”
Section: Experiments 2: the Effects Of Ofq Or An Agonist For The Orl-1mentioning
confidence: 99%
“…Concentrations of LH were determined in duplicate 100-or 200-l aliquots by RIA, using a modification of a previously described method (27). Values are expressed in terms of the ovine standard, NIH S24.…”
Section: Riasmentioning
confidence: 99%
“…This suggests that DA receptors may be involved in the VIP modulation of GnRH secretion in the septo-preoptic area and may influence interactions involved in mediating the photoperiodic response in birds. In mammals, it has been suggested that the dopaminergic system interacts with photoperiodic regulation of LH secretion [69, 70]. …”
Section: Discussionmentioning
confidence: 99%